Meningkatkan Minat Belajar Bahasa Arab Dengan Metode Ice Breaking Di Madrasah Aliyah Al-Amiriyyah Banyuwangi - Abdul Basith; Ana Masruroh (TADRIS AL-ARABIYAT: Jurnal Kajian Ilmu Pendidikan Bahasa Arab, 2023)
The aim of this research: First, to describe the forms of implementing ice breaking to increase interest in learning Arabic at Madrasah Aliyah Al Amiriyyah Blokagung Tegalsari Banyuwangi. Second, to find out how to prepare for the application of ice-breaking to increase interest in learning Arabic at Madrasa Aliyah Al-Amiriyyah Blokagung Tegalsari Banyuwangi. Third, to find out the evaluation of the application of ice-breaking to increase interest in learning Arabic at Madrasah Aliyah Al-Amiriyyah Blokagung Tegalsari Banyuwangi. The method used in this research is descriptive qualitative, their research design uses inductive data analysis (meaning that specific data is then used to draw general conclusions). The data collection used is by interview, observation, and documentation based on research results and discussion. The result of the research shows that the application of ice breaking at Madrasah Aliyah Al-Amiriyyah Blokagung Tegalsari Banyuwangi is very effective in increasing interest in learning Arabic. In addition, this study also concluded that: 1). there are 3 forms of ice breaking used in Madrasah Aliyah Al-Amiriyyah to increase interest in learning Arabic, namely the type clapping, guessing pictures, and singing. 2). Things that need to be prepared to carry out ice-breaking activities include: a). Determine the form of ice breaking that will be used, b). Prepare ice-breaking materials as needed. c). Prepare media or tools to be used, d). Trial, e). Consider interactions with students, f). Involve all students, g). Pay attention to the length of the times or duration of ice-breaking, h). Make sure students feel comfortable. i). Do a review. 3) evaluation of the application of Ice breaking is carried out once every three weeks in oral or written form.